Development of panoramic scanning device of mine ore-pass - SHI Zhi-jun; LIU Yan-zhang; YE Yi-cheng; TU Fu-quan; ZHAO Wei; ZHANG Xu; YANG Ke-ni (Gong-kuang zidonghua, 2013)
In view of problems that manual checking ore-pass method cannot observe wall of mine ore-pass clearly and has hidden danger, a panoramic scanning device of mine ore-pass was designed, which was composed of data collection system, hoisting system, positioning system of ore-pass depth and data processing and video monitoring system. The data collection system collects image data of wall of ore-pass through four symmetrically arranged cameras, the image data is transmitted to the data processing and video monitoring system through gigabit network line after processed by gigabit network exchanger. The data processing and video monitoring system expanses the image of the wall and displays it on video monitoring interface. The positioning system of ore-pass depth collects depth information of scanning probe in ore-pass, and positioning program of ore-pass depth calculates depth of the scanning probe in the ore-pass according to circumference of number axis and the depth information. Actual test result shows that the device can realize panoramic scanning for ore-pass with high-depth, large-diameter and lightless.